ANTESEDEN MINAT BERWIRAUSAHA GENERASI MUDA - Dewi, Desak Gede Listya; Manuati Dewi, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
The percentage of unemployment at the university level in Indonesia is high at 7.35%. Thus, efforts are needed so that students increase their interest in entrepreneurship to reduce the unemployment rate due to the opening of new jobs, at least for the students concerned. The purpose of this study was to analyze the effect of entrepreneurial attitudes, entrepreneurial knowledge and entrepreneurial self-efficacy on young generation's entrepreneurial interest. The research location is the Faculty of Economics and Business, Udayana University, Denpasar. The sample used was 312 people. This study used purposive sampling as the determination of the number of samples and data collection was carried out by distributing questionnaires. The data analysis technique used is descriptive and inferential analysis, namely Multiple Linear Regression. The results of the analysis show that entrepreneurial attitudes, entrepreneurial knowledge and entrepreneurial self-efficacy have a positive and significant effect on entrepreneurial interest. The theoretical implications of this research provide evidence on the development of organizational behavior science and management science, especially regarding entrepreneurial attitudes, entrepreneurial knowledge. Meanwhile, practically this research can be used as a reference in an effort to increase interest in entrepreneurship for the younger generation